STRATEGI PENINGKATAN MANAJEMEN DIRI PASIEN PENYAKIT GINJAL TAHAP AKHIR YANG MENJALANI HEMODIALISIS - Fida' Husain; Ida Nur Imamah; Dadi Hamdani (Jurnal Ilmu Keperawatan Medikal Bedah, 2022)
End-stage kidney disease (ESRD) has an impact on the sufferer's physical, psychological, social, and spiritual well-being. These problems can reduce the quality of life of ESRD patients undergoing hemodialysis. This requires the patient to be fully involved, both in management and therapeutic decision-making, symptom management, and self-care. This literature review aims to describe various programs to improve the self-management skills of ESRD patients undergoing hemodialysis. The articles used in this literature review are sourced from the CINAHL, MEDLINE, and Google Scholar electronic databases with the keywords self-management, self-care, adherence, ESRD, and hemodialysis with inclusion criteria: published in 2015-2020, full text, using English or Indonesian, and experimental studies conducted on hemodialysis patients. Eight articles were obtained discussing programs that can be used to improve self-management of ESRD patients undergoing hemodialysis, including education and counseling programs, self-management programs, self-efficacy training, self-monitoring programs, and social support. The differences between each program include the time and technical implementation, while the similarities are that each program cannot be separated from education for providing health information to patients. Providing structured education and involving social support can be used as a program to improve self-management in ESRD patients undergoing hemodialysis.